Ensiling and thermic treatment effects on ruminal carbohydrate fermentation and post-ruminal crude protein concentration in partial-crop peas and faba beans - M. Bachmann; P. Okon; F. Pilger; C. Kuhnitzsch; S.D. Martens; O. Steinhöfel; A. Zeyner (Journal of Applied Animal Nutrition)
This study was conducted to examine effects of ensiling, toasting or ensiling plus toasting in partial-crop field peas and faba beans harvested each with 375 g dry matter/kg (Biologische Bundesanstalt, Bundessortenamt und Chemische Industrie (BBCH) scale 79 and 81, respectively) on gas production and post-ruminal crude protein (PRCP) concentration by in vitro incubation in ruminal fluid batch-cultures. The silages made from partial-crop field peas and faba beans (Rostock Model Silages) had a pH of 4.3 and 4.6, respectively, and were not typically lactic acid dominated. The silages remained stable after opening for 100 h (peas) and 168 h (faba beans). Toasting was simulated in a drying oven at 160 °C for 60 min. Post-incubation pH and gas accumulation profiles were little affected by treatment. Ensiling did not alter effective PRCP. Toasting and ensiling plus toasting increased effective PRCP up to 25 and 20%-points in peas and up to 35 and 11%-points in faba beans, respectively. Ensiling increased non-protein nitrogen and soluble protein concentration, whilst toasting decreased soluble protein. Significant correlations existed between protein fraction B3 (neutral detergent-insoluble protein) and effective PRCP (r≥0.84; P<0.05) and fraction C (acid detergent-insoluble protein) and effective PRCP (r≥0.79; P<0.05). Ensiling and toasting both decreased arginine and lysine levels. It was concluded that partial-crop peas and faba beans with BBCH 79 and 81, respectively, can provide readily available nutrients and high-quality fibre in the residual plant. However, preserving by ensiling required balance between the reduction of non-protein nitrogen and fermentability characteristics. Toasting reduced protein solubility and increased PRCP, but it was not clear if PRCP was usable for ruminants or was partially bound into Maillard polymers.